PENGARUH SPORT MASSAGE DAN PENYINARAN RADIASI INFRAMERAH TERHADAP PENURUNAN KADAR ASAM LAKTAT ATLET FUTSAL - Meilana Saeful Rizal, - (2022)
This study aims to determine the effect of sport massage and infrared irradiation on reducing lactic acid levels in futsal athletes. This study uses a true experimental method with a two-group pretest posttest design model. 20 male athletes of UKM Futsal Universitas Pendidikan Indonesia made the research subject using purposive sampling technique. The procedure of this research is to provide high-intensity exercise activities using the Yo-Yo Intermittent Recovery Test to increase lactic acid levels which is then carried out with the Accutrend lactacid test, after which the athletes are given sports massage and infrared radiation irradiation for a duration of 15 minutes, then the Accutrend lactacid test is carried out again. . The research instrument used in this study is Accutrend lactacid, which is a tool that serves to determine the level of lactic acid in someone who is exercising. Based on the results of data processing, it was found that the sports massage method and infrared radiation irradiation had a significant effect on reducing lactic acid levels, and it was known that the results of the comparison that the infrared radiation irradiation method with sport massage had no significant difference in reducing lactic acid levels. Keywords: infrared, lactic acid level, sport massage